Korelasi PBL Dengan Keterampilan Berpikir Siswa Kelas X Tentang Kesetaraan Gender Di SMAN 4 Palangka Raya - Patricia Angelina; Paulina Maria Ekasari Wahyuningrum; Silvester Adinuhgra (Sepakat : Jurnal Pastoral Kateketik, 2023)
This study aims to identify and describe the relationship between the Problem-Based Learning learning model and students' critical thinking skills at SMA Negeri 4 Palangka Raya. The formulation of the research problem is whether there is a relationship between the problem-based learning model and critical thinking skills about gender equality in class X students at SMAN 4 Palangka Raya; how big is the relationship between problem-based learning models and critical thinking skills about gender equality in students of SMAN 4 Palangka Raya; and what is the perception of students of SMAN 4 Palangka Raya on the effectiveness of the problem-based learning model in improving critical thinking skills about gender equality. The research approach uses a quantitative approach to this type of correlational research. Respondents to this study were 18 class X class Catholic students at SMAN 4 Palangka Raya, conducted from 9 to 23 June 2023. Data was collected through a questionnaire divided into two parts in form, namely problem-based learning and critical thinking skills about gender equality, with very good (4), good (3), pretty good (2), and not good (1) alternative answers. Data analysis techniques use Product Moment correlation in data collection to determine the relationship between two interval symptoms, such as values. The results of calculations on the research hypothesis that rxy (0.605) > table (0.497) from a significant level of 5% conclude that there is a relationship between the Problem-Based Learning model and critical thinking skills about gender equality in class X students at SMA Negeri 4 Palangka Raya. This result shows that the Problem-Based Learning learning model is one factor that influences and plays a role in improving students' critical thinking skills about gender equality. So, it can be expected that this research will be useful for school principals and Catholic Religious Education teachers so that they continue to support and be able to use learning models that can create a comfortable and creative classroom atmosphere.